Comparative efficacy of virtual reality headset and auditory distraction for reducing anxiety and pain during inferior alveolar nerve block in 7–10-year-old children: a clinical trial - Zahra Bahrololoomi; Kazem Vaez; Amene Hosseini Yekani; Maryam Irannezhad; Zahra Parvizi (BMC Pediatrics)
Abstract Objectives Pain and anxiety are not limited to a certain age group; however, their thresholds are closely correlated with age, and they can cause irreversible mental disorders in children. This study compared the efficacy of a virtual reality (VR) headset and auditory distraction for reducing anxiety and pain in 7- to 10-year-old children during inferior alveolar nerve block (IANB) injection. Materials and methods This randomized clinical trial included 45 patients who required an IANB. The children were randomly assigned to 3 groups (n = 15) to use a VR headset, headphones, or no distraction (control) during the IANB. The pain experienced by the children during the injection was quantified subjectively using the Wong-Baker FACES pain rating scale (WBFPS) and objectively using the Face Leg Activity Cry Consolability (FLACC) scale. Anxiety was quantified subjectively using the Facial Image Scale (FIS) and objectively by measuring changes in heart rate (HR) and blood pressure (BP). The data were analyzed using SPSS 19 (alpha = 0.05). Results The mean age of the patients was 8.31 ± 1.07 years. There were no significant differences in age or sex distribution among the three groups (P > 0.05). Significant differences were found in the FLACC (P = 0.000), WBFPS (P = 0.011), and FIS (P = 0.020) scores after the injection among the three groups; the headphone group had the highest scores, and the VR group had the lowest scores. The mean change in systolic BP was significantly different among the three groups (P = 0.00), and the VR headset group experienced the smallest increase in BP. The differences in diastolic BP (P = 0.291) and HR changes were not significant among the groups (P = 0.062). Conclusion Using a VR headset significantly decreased anxiety and pain during the IANB, while using headphones had no particular advantage. Trail registration This trial has been approved by the ethics committee of the university (IR.SSU.DENTISTRY.REC.1401.072) and then prospectively registered on The Iranian Registry of Clinical Trials (IRCT20230614058486N1) on 24 June 2023.